Implementation of a hybrid AC-AC direct power converter with unity voltage transfer - Wijekoon, Thiwanka; Klumpner, Christian; Zanchetta, Pericle; Wheeler, Patrick (IEEE, 2008)
This paper presents a novel hybrid direct power converter (HDPC) which overcomes the two main disadvantages of matrix converters: limited voltage transfer ratio and low immunity to grid disturbance. The proposed converter is formed by integrating a reversible auxiliary boost converter in the dc link of the two-stage matrix converter. Therefore, the HDPC can provide unity voltage transfer ratio even in the case where the supply voltage is highly unbalanced. The proposed converter also preserves most of the inherent advantages of the conventional matrix converter such as: controllable input power factor, sinusoidal supply currents, and bidirectional power flow. A novel predictive current control technique for the HDPC is also proposed for minimum energy storage in the converter. Important aspects of design, control, and implementation of the new HDPC are presented including theoretical analysis and simulations. Experimental waveforms at unity voltage transfer using a laboratory prototype are presented to confirm the viability of the proposed idea.